2016
DOI: 10.1021/acs.jced.5b00830
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Viscosities, and Refractive Indices of Dimethyl Carbonate + 1-Hexanol/1-Octanol Binary Mixtures at Different Temperatures

Abstract: The densities, viscosities, and refractive indices for the binary mixtures of dimethyl carbonate (DMC) + 1-hexanol/1-octanol were measured at atmospheric pressure and temperature of 293.15, 298.15, 303.15, 308.15, 313.15, 318.15, and 323.15 K over the whole concentration range. Different thermodynamic, transport, and optical properties, such as excess molar volume, partial molar volume, thermal expansion coefficient, isothermal coefficient of pressure excess molar enthalpy, activation energy of flow, excess re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The deviations of the experiment and literature values are calculated and listed in Table . From Table , for [C 2 mim]­[NTf 2 ], the absolute density deviations are less than 0.03% in the literature except for those in ref (but the absolute deviations are still less than 0.14%); the absolute viscosity deviations are less than 6.6% in the literature. ,, For [C 4 mim]­[NTf 2 ], the absolute density deviations are higher than 0.04% and less than 0.18% in the literature; the absolute viscosity deviations are higher than 1.2% and less than 4.1% in the literature. , For DMC, the absolute density deviations are less than 0.10% in the literature except one point, 0.139%; the absolute viscosity deviations are less than 10% in the literature , except for one point, 15.556% . For DEC, the absolute density deviations are less than 0.03% in the literature , except for two points, 0.132% and 0.115%; the absolute viscosity deviations are less than 2.4% in the literature. , …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The deviations of the experiment and literature values are calculated and listed in Table . From Table , for [C 2 mim]­[NTf 2 ], the absolute density deviations are less than 0.03% in the literature except for those in ref (but the absolute deviations are still less than 0.14%); the absolute viscosity deviations are less than 6.6% in the literature. ,, For [C 4 mim]­[NTf 2 ], the absolute density deviations are higher than 0.04% and less than 0.18% in the literature; the absolute viscosity deviations are higher than 1.2% and less than 4.1% in the literature. , For DMC, the absolute density deviations are less than 0.10% in the literature except one point, 0.139%; the absolute viscosity deviations are less than 10% in the literature , except for one point, 15.556% . For DEC, the absolute density deviations are less than 0.03% in the literature , except for two points, 0.132% and 0.115%; the absolute viscosity deviations are less than 2.4% in the literature. , …”
Section: Resultsmentioning
confidence: 88%
“…The density and viscosity of the pure compounds [C 2 mim]­[NTf 2 ], [C 4 mim]­[NTf 2 ], DMC, and DEC from this study and available from the literature are shown in Table . , The measured values of the binary mixtures are listed in Tables and . All of the values of the density and viscosity were measured at atmospheric pressure ( p = 101.3 kPa).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of these molecular interactions, generated due to deviation of components properties in solution from those in pure forms, can describe the solution behavior. 15 Therefore, the molecular associations observed at different temperatures are significant for development of molecular models for predicting the solution behavior. Moreover, the thermophysical data for nonelectrolyte liquid−liquid mixtures can provide valuable information for designing different industrial operations such as heat transfer, mass transfer, and separation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation on thermophysical properties for a binary blend at different temperatures would reveal the type and nature of involved molecular interactions. The analysis of these molecular interactions, generated due to deviation of components properties in solution from those in pure forms, can describe the solution behavior . Therefore, the molecular associations observed at different temperatures are significant for development of molecular models for predicting the solution behavior.…”
Section: Introductionmentioning
confidence: 99%